Lactobacillus gasseri PA-3 directly incorporates purine mononucleotides and utilizes them for growth. (28th February 2022) - Yamada, N.; Saito, C.; Kano, H.; Fukuuchi, T.; Yamaoka, N.; Kaneko, K.; Asami, Y.
Abstract: Lactococcus lactis has been reported unable to directly incorporate mononucleotides but instead requires their external dephosphorylation by nucleotidases to the corresponding nucleosides prior to their incorporation. Although Lactobacillus gasseri PA-3 (PA-3), a strain of lactic acid bacteria, has been found to incorporate purine mononucleotides such as adenosine 5'-monophosphate (AMP), it remains unclear whether these bacteria directly incorporate these mononucleotides or incorporate them after dephosphorylation to the corresponding nucleosides. This study evaluated whether PA-3 incorporated radioactively-labeled mononucleotides in the presence or absence of the 5'-nucleotidase inhibitor α, β-methylene ADP (APCP). PA-3 took up 14 C-AMP in the presence of APCP, as well as incorporating 32 P-AMP. Furthermore, radioactivity was detected in the RNA/DNA of bacterial cells cultured in the presence of 32 P-AMP. Taken together, these findings indicated that PA-3 incorporated purine mononucleotides directly rather than after their dephosphorylation to purine nucleosides and that PA-3 utilizes these purine mononucleotides in the synthesis of RNA and DNA. Although additional studies are required to identify purine mononucleotide transporters in PA-3, this study is the first to show that some lactic acid bacteria directly incorporate purine mononucleotides and use them for growth.